The Mixture of Molybdate and Ethoxylated Fatty Amines as Corrosion Protection in SAW Weld Joints of API 5L X-52 Pipeline Steel 3.5% NaCl Solution: Electrochemical Study - Hery Tristijanto; Mochammad Noer Ilman; Priyo Tri Iswanto (Politeknik Negeri Lhokseumawe, 2023)
Steel widely used as pipelines in oil and gas transmission was susceptible to corrosion attack. In the present study, the corrosion inhibitions of sodium molybdate (SM) and ethoxylated fatty amine (EFA) for corrosion of carbon steel (API 5L X-52 steel welded pipelines) at base metal (BM), weld metal (WM), and heat affected zone (HAZ) in 3.5% NaCl solution was studied experimentally using potential dynamic polarization and electrochemical impedance spectroscopy (EIS). The results indicated that Tafel polarization investigations showed that the corrosion potentials shift to a positive direction in the BM, HAZ, and WM areas, and the corrosion rate density moves to the left. The decreased corrosion rate was related to form a passive film on the steel surface. Electrochemical impedance spectroscopy (EIS) measurements show that two-time constants appear, the first in the mid-high frequency range related to the corrosion process between the metal surface and Mo ions. The second in the low-frequency range is related to the formation of the two metal layers, Oxide/hydroxide. Thus, the corrosion protection of steel has been confirmed. The most excellent inhibitor efficiency, when the concentration of the SM was 0.4%, and EFA was 400 ppm, occurred in BM, WM, and HAZ, respectively